Leukemia-Associated, Constitutively Active Mutants of SHP2 Protein Tyrosine Phosphatase Inhibit NF1 Transcriptional Activation by the Interferon Consensus Sequence Binding Protein - Huang, Weiqi (American Society for Microbiology, 2006)
Deficiency in either the interferon consensus sequence binding protein (ICSBP) or neurofibromin 1 (Nf1) increases the proliferative response of myeloid progenitor cell to hematopoietic cytokines. Consistent with this, we previously demonstrated that ICSBP activates transcription of the gene encoding Nf1 (the NF1 gene). In the studies presented here, we determine that ICSBP tyrosine phosphorylation is necessary for the activation of NF1 transcription. Since ICSBP is tyrosine phosphorylated in response to hematopoietic cytokines, these studies identify a novel pathway by which cytokine-induced posttranslational modification of ICSBP results in NF1 transcription. Nf1 subsequently inactivates cytokine-activated Ras, thereby creating a negative feedback mechanism for cytokine-induced proliferation. In these studies, we also determine that ICSBP is a substrate for SHP2 protein tyrosine phosphatase (SHP2-PTP). We find that wild-type SHP2-PTP dephosphorylates ICSBP only in undifferentiated myeloid cells. In contrast, a leukemia-associated, constitutively activated mutant form of SHP2-PTP dephosphorylates ICSBP in both myeloid progenitors and differentiating myeloid cells. Activated SHP2-PTP mutants thereby inhibit ICSBP-dependent NF1 transcription, impairing this negative feedback mechanism on cytokine-activated Ras. Therefore, these studies suggest that leukemia-associated ICSBP deficiency cooperates with leukemia-associated activating mutants of SHP2-PTP to contribute to the proliferative phenotype in myeloid malignancies.